New Aspects in the Mechanical Behavior of a Polycarbonate Found by an Experimental Study - Alfredo Alán Rey Calderón; Alberto Díaz Díaz (Advances in Materials Science and Engineering)
The aim of this paper was to analyze in detail the mechanical behavior of a polycarbonate by means of uniaxial tensile and compressive tests and to reveal new key aspects that must be taken into account in any predictive model. Uniaxial monotonic and creep-recovery tests were carried out at a variety of temperatures, stress levels, and load rates to get a complete description of the material response. Prior to mechanical testing, the material was subjected to a thermal rejuvenation in order to eliminate any previous aging and to obtain reliable and useful results. In every test, a complete determination of the strain state was assured by measuring axial and transverse strains with strain gauges. During the tests, significant asymmetry effects and viscous phenomena already reported by other authors were confirmed. The newest finding is that a nonlinear master transverse strain/axial strain curve matches perfectly with the experimental curves. This master curve is temperature- and rate-independent. Another originality of this paper is the disclosure of an instantaneous, hypoelastic-like behavior at high strain rates. The experimental observations presented in this study should be incorporated by a theoretical model whose aim is to accurately predict the mechanical behavior of polycarbonate subjected to any 3D stress state.